IMPLEMENTASI PERANGKAT TEXT-TO-SPEECH PEMANGGIL SISWA MANDIRI BERBASIS NATURAL LANGUAGE PROCESSING DI MIT BAKTI IBU KOTA MADIUN - Ardian Prima Atmaja; Sigit Kariagil Bimonugroho; Tri Septianto; Mochamat Bayu Aji; M. Shafwallah Al. Aziz R; Dimas Adi Saputra (Jurnal Hilirisasi IPTEKS, 2023)
Madrasah Ibtidaiyah Terpadu (MIT) Bakti Ibu is one of the highly sought-after elementary schools in the city of Madiun and its surrounding areas. The busiest time occurs during the pick-up after school hours, as it involves interactions between the pick-up persons and many students. The school has provided staff to call out each student who has been picked up by their respective guardians. However, this process is deemed inefficient as it heavily relies on the performance of the staff at that moment, which may not always be optimal. The objective of this activity is to enhance efficiency in calling the students. It involves implementing an independent student-calling Artificial Intelligence (AI) device based on Natural Language Processing (NLP) technology, utilizing Text-to-Speech (TTS) technology embedded in a Mini PC platform running a Linux operating system with a touch screen connected to a server via the internet. The activity takes place at Madrasah Ibtidaiyah Terpadu (MIT) Bakti Ibu in Banjarejo Sub-district, Taman District, Madiun City, East Java. The activity methodology includes preparation, demonstration, evaluation, and mentoring stages. The outcome of this activity is that the TTS technology enables computers to convert text into speech that can be heard by humans. This technology is utilized to aid or even replace the role of staff in calling students who have been picked up by their guardians at the school, based on student name data stored in the database server.